Field programmable gate array based three-phase PWM inverter - Mekhilef, Saad; Rahim, N.A. (2002)
The three-phase Pulse Width Modulation PWM generation is the heart of the inverter system. Its main function is to control the switching sequence of the power devices according to per-loaded instruction. Using Field Programmable Gate Array (FPGA) technology all the functions can be implemented in a single chip. The implementation tool fit the entered design into the target device (XC4008E). It will compile a design file into a configuration file that is optimized using logic gates and interconnections for the target device. Design verification includes functional simulator, circuit testing and timing simulation are the main functions to verify the proper operation of the designed circuit. Foundation series M1.S has been used in this work. This Xilinx development tools converts the design idea into a configuration data file, which could be loaded into Xilinx FPGA.